THE SYNERGY OF ECONOMIC LAW AND HEALTH LAW IN HANDLING PETTY THEFT OFFENDERS: A REVIEW OF THE PROTECTION OF BASIC RIGHTS OF OFFENDERS - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research discusses the importance of synergy between economic law and health law in handling petty theft offenders, especially in the context of protecting the basic rights of offenders. So far, the handling of petty theft cases in Indonesia is still dominated by conventional criminal law approaches that do not consider economic factors and the health conditions of the perpetrators, especially for those from vulnerable groups. Through a normative legal research method with a literature approach, this study examines legislation, policies, and related literature, such as the Criminal Code, PERMA No. 2 of 2012, and Law No. 11 of 2012 concerning SPPA. The results of the study show that restorative justice and diversion policies are progressive steps in providing protection for the basic rights of offenders, but their implementation still faces various challenges, such as lack of coordination across sectors, limited resources, and not optimal integration of economic programmes and health services in the legal process. This study recommends the need to strengthen synergies between legal, economic and health policies, as well as regulatory updates that are more responsive to the needs of offenders, so that the protection of basic rights can be realised optimally and equitably.